Body Image and Appearance: The Ultimate Teen Guide - Gay, Kathlyn, (Rowman & Littlefield Publishers, 2009)
Body image is a pervasive preoccupation for almost all teens. Nearly every teen has dealt with issues of height, weight, skin, and other features. And many teens have undertaken diets, engaged in body building programs, or resorted to surgery to alter their appearances. In Body Image and Appearance: The Ultimate Teen Guide, author Kathlyn Gay addresses all of these concerns to provide teens with a healthy way to think about themselves. This book tackles such topics as the cultural standards of what a 'perfect' body should look like, methods for changing appearances, and matters related to height, such as dwarfism and height discrimination. Throughout the book, Gay offers advice on how teens can learn to be comfortable with their bodies and move beyond unhealthy preoccupations with size and appearance.